Age-related differences in spontaneous trait judgments from facial appearance. Issue 5 (3rd September 2018) - Smailes, Harriet L.; Humphries, Joyce E.; Ryder, Hannah; Klatt, Thimna; Maltby, John; Pearmain, Alice M.; Flowe, Heather D.
Abstract : We tested whether there are age-related declines in detecting cues to trustworthiness, a skill that has been demonstrated to be rapid and automatic in younger adults. Young ( M age  = 21.2 years) and older ( M age  = 70.15 years) adults made criminal appearance judgments to unfamiliar faces, which were presented at a duration of 100, 500 or 1, 000 ms. Participants' response times and judgment confidence were recorded. Older were poorer than young adults at judging trustworthiness at 100 ms, and were slower overall in making their judgments. Further, the cues (i.e. perceptions of anger, trustworthiness and happiness) underlying criminality judgments were the same across age groups. Judgment confidence increased with increasing exposure duration for both age groups, while older adults were less confident in their judgments overall than their young counterparts. The implications are discussed.